Função da legítima sucessória - Ortigosa, Ana Lúcia Macéa (2024)
This work aims to highlight the institute of legitimate succession and the functions it performs in society. To achieve the desired depth, the origin of the law was analyzed, which dates to the time when the Democratic Rule of Law did not exist, not even in the form of an idealization by the great scholars of the time. Later, the work raises the relevance and great influence that the Roman Empire had on the Brazilian legislator. Finally, the concept, composition, scope, consequence and function, in general, of the reserved portion of an estate in Brazil's legal system was explored. And, finally, a case law, recent and much commented on by legal scholars, from the Superior Court of Justice was highlighted, which briefly makes objective and concrete notes on specific aspects of Succession Law, particularly the theme of the dissertation, which culminates with the absolute closure of work